Metaphors as proxies for identity: a case study of a teaching English to young learners (TEYL) teacher - Norhakimah Khaiessa Ahmad,; Arshad Abd Samad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Metaphor and metaphorical expressions are phenomena of interest in teacher education research and research on teacher identity. However, little attention has been given to teaching of English to young learners (TEYL) teachers’ metaphorical expressions, and what these expressions might tell us about their identities and experiences. This study explores the metaphorical expression constructed by an experienced teacher to describe what it means to be a TEYL teacher in the ESL context. Data were gathered from semi-structured interviews, stimulated recall interviews, and a metaphor elicitation prompt: ‘Who do you see yourself as a teacher?’ The results revealed that while the metaphorical expression of ‘mother’ stands out as a concept that associates teaching with being nurturing, the teacher’s enactment of other roles; projected as ‘knowledge provider’, ‘law enforcer’, and ‘facilitator’, is more strongly oriented to the behaviourist idea of teaching. These findings shed light on the role of identity in expanding the in-service teachers’ perspective of teachers and teaching using selfconstructed metaphors. A major recommendation of this study is that teacher educators need to promote reflective practice in TESL teacher training to critically explore the concept of knowledge about self.